A Public Health Approach to Addressing Arthritis in Older Adults: The Most Common Cause of Disability - Hootman, Jennifer M. (American Public Health Association, 2012)
Arthritis is highly prevalent and is the leading cause of disability among older adults in the United States owing to the aging of the population and increases in the prevalence of risk factors (e.g., obesity). Arthritis will play a large role in the health-related quality of life, functional independence, and disability of older adults in the upcoming decades. We have emphasized the role of the public health system in reducing the impact of this large and growing public health problem, and we have presented priority public health actions.